The Influence of Lifestyle, Financial Technology, And Financial Literacy on Millenials’ Digital Gold Investment Decisions - Rahmasari, Adelia Gita; Sumiati (Jurnal Management Risiko dan Keuangan, 2025)
Investment decisions are long-term processes that require careful consideration, involving the allocation of funds to specific assets with the goal of generating returns and maintaining financial stability in the future. This study is urgent due to the rising trend of digital gold among millennials in the post-pandemic era. This study aims to examine the influence of lifestyle, financial technology, and financial literacy on the decision of millennials in Malang City to invest in digital gold. As explanatory research, it explains causal relationships among variables through hypothesis testing. Using a non-probability sampling method with purposive sampling technique, 120 respondents were selected. The data were analyzed using multiple linear regression in SPSS version 27. The results show that lifestyle, financial technology, and financial literacy have a positive and significant effect on investment decisions, both partially and simultaneously. The results show that lifestyle, financial technology, and financial literacy significantly and positively affect investment decisions. The novelty of this study lies in linking behavioral, technological, and financial literacy aspects to explain digital gold investment. The findings suggest that both platforms and investors can apply these insights to support wiser investment choices.